Surgical Repair of a Quadricuspid Aortic Valve With Severe Regurgitation Utilizing “Tricuspidization” and Annular Banding: A Case and Technique Details Report - Yu, Yang; Huang, Ruixuan; Ding, Zheng; Shi, Enyi; Gu, Tianxiang (Frontiers in Cardiovascular Medicine, 2022)
The quadricuspid aortic valve (QAV) is a rare congenital disease with a prevalence of 0.013% to 0.043% of cardiac cases. Most patients with QAV are treated with aortic valve replacement. A Type B QAV with dilated ascending aorta of 47.9 mm; combined with severe regurgitation is reported here. In this case, considering the patient`s cusps are flexible and reservable, the aortic root was reconstructed utilizing tricuspidization and annular banding technique, and dilated ascending aorta was replaced at the same time